Pengaruh Diferensiasi, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Kopi Liberika (Studi Pada Konsumen Kopi Liber.Co Di Kota Sambas) - Nur Fajar Febtysiana; Dody Radiansah; Revi Sesario (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
The research aims to determine the influence of differentiation, product quality, and decision on buying coffee powder and drink of liberica product. The research was conducted on June to September 2022 at the Liber.Co Coffee Shop (small size enterprises) in city of Sambas. The research is expected to provide information about the factors that influence on making decision in buying coffee powder and drink of liberica product. The research location was purposive. The method was case study with Slovin sample method. The sample size was 75 consumers. The data resources were primary and secondary data. The primary data was collected by observation, questioners, and interview. The data analysis was descriptive with SPSS Windows ver. 24.0 as tool of analysing statistical data. The technique was multiple linear regression analysis. The results showed that the differentiation, Product Quality, and Price influenced significantly on purchasing decisions for coffee powder and drinks of liebrika simultaneously. Partially, the differentiation of coffee powder and drinks of lieberika did not influence significantly. The quality of coffee powder of liebrica product influenced significantly, and coffee drink product was not influence significantly. Price variable of coffee powder and drink of lieberica influenced significantly. The result of R square was 0.395 which indicated that 39.5% of purchasing decisions of coffee powder of lieberica were influenced by differentiation, product quality and price. The result of R square was 0.489 which indicated that 48.9% of purchasing decisions of coffee drink was influenced by differentiation, product quality and price.